Effects of Reducing Dietary Net Energy on Growth Performance and Carcass Characteristics of Grow-Finish Pigs - Rafe Q. Royall; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Carine M. Vier; Matthew Spindler; Uislei Orlando; Luis Zaragoza; Ning Lu; Wayne Cast; et al. (Kansas Agricultural Experiment Station Research Reports, 2024)
This study was conducted to evaluate the effect of dietary net energy (NE) on growth performance, carcass characteristics, and removal and mortality rates of grow-finish pigs and compare different net energy (NE) systems by using caloric efficiency. A total of 1,927 pigs (initially 51.5 ± 0.52 lb) were used in a 125-d study. Pens of pigs were blocked by BW and randomly allotted to one of five dietary treatments of decreasing NE. There were 23 to 26 pigs per pen and 15 replications per treatment in a randomized complete block design. The highest NE diet (control) was a corn-soybean mealbased diet. Based on NRC (2012) ingredient NE values, the lowest energy diet contained 8% less NE than the control through inclusion of 25% wheat middlings and 15% DDGS (6% oil). These diets were blended to achieve intermediate NE levels (2, 4, and 6% less NE than the control). Dietary phases were fed from approximately 50 to 90, 90 to 130, 130 to 180, 180 to 230, and 230 to 300 lb, respectively. Overall, reducing NE decreased (linear, P < 0.001) ADG and final BW, but increased (linear, P < 0.001) ADFI, resulting in poorer (linear, P < 0.001) feed efficiency. Reducing NE worsened (linear, P < 0.001) caloric efficiency (CE) based on NRC ingredient loading values, improved (linear, P ≤ 0.003) CE based on INRA (2008) or Brazilian Tables for Poultry and Swine (2017) ingredient loading values. However, when formulating diets using CVB (2020) ingredient loading values, reducing NE resulted in no evidence of difference (P > 0.10) in CE. For carcass characteristics, reducing NE decreased (linear, P < 0.001) HCW, backfat depth, and carcass yield. However, reducing NE increased (linear, P < 0.001) percentage lean. Moreover, reducing NE tended to increase (linear, P = 0.073) percent removals, with no evidence of difference (P > 0.10) on percent mortality. When considering CE on a carcass gain basis, reducing NE worsened (linear, P ≤ 0.004) CE based on NRC or CVB ingredient loading values, while reducing NE improved (linear, P < 0.001) CE based on INRA ingredient loading values. However, reducing NE resulted in no evidence of difference (P > 0.010) in CE based on Brazilian Tables ingredient loading values. These results would suggest that the NRC database overestimates NE contributions of fibrous ingredients such as wheat middlings and corn DDGS, while the INRA database underestimates their contributions to NE, whether CE is calculated based on live or carcass gain. Meanwhile, NE values in the CVB database appear to value NE more accurately in these diets based on live gain but underestimate their value on a carcass basis. The Brazilian tables appear to underestimate the contributions of fibrous ingredients to dietary NE on a live basis, but more accurately value their contributions on a carcass basis. Thus, this study reinforces establishing and utilizing accurate energy values of ingredients to economically value them appropriately.
Keywords: Caloric efficiency; energy; grow-finish pigs